An integrated cash waqf and Islamic crowdfunding model (I-CWCM) for SMEs: Policy implications for the post-Covid-19 pandemic - Sulaeman; Abbiyu Muhamad Ghozali (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – This paper aims to discuss the proposed model, called Integrated Cash Waqf and Islamic Crowdfunding Model (I-CWCM), for small and medium enterprises (SMEs), including micro-enterprises and household businesses in the digital era.Methodology – The author documents some cash waqf models and Islamic crowdfunding models that have been developed by previous researchers. And then modified and introduces the I-CWCM model based on the relevant literature study.Findings – In this model, the cash waqf funds (temporary and perpetual) will be invested in Islamic investments and productive asset programs. The investment return gained from cash waqf investments will be utilized for providing financial services by using PLS financing schemes and non-PLS financing schemes for SMEs.Implications – The article is conceptual in nature, and the developed model has not been tested either through interviews or empirical testing. For further research, it is necessary to validate the model either through interviews or by developing hypotheses. Furthermore, the I-CWCM will be possible to set up Islamic social finance institutions, Islamic financial institutions, and Islamic microfinance institutions in a country with a majority Muslim population like Indonesia, especially in times of crisis such as Covid-19 outbreaks.Originality – The originality of this study is the I-CWCM will include two important unit funds: (1) the reserve fund is for sustaining the cash waqf founder, and (2) the backup risk fund is for addressing any risk in business and non-business financing activities.